The Association of VDR/FokI Gene Polymorphism and Protein Expression With Histopathological Alterations in Patients With Thyroid Colloid Nodule - Mariwan F. Abdalfatah; Abdullah A. Shareef; Lana S. Saleh; Mustafa F. Rajab; Shukur W. Smail; Saman S. Abdulla; Harem Khdir Awla; Rivan H. Ishaac; Kazhal S. Ibrahim; Mazyar J. Ahmed; Fairuz A. Kakasur; Khder Hussein Rasul (Analytical Cellular Pathology)
Conclusion: Our results reveal prominent cytoplasmic VDR expression, suggesting a distinct distribution pattern and offering valuable insights into its potential role in colloid nodules. VDR expression increases with increasing size and number of nodules. Regarding FokI genotypes, TT genotype was less likely to develop colloid nodule. These findings contribute to our understanding of cellular characteristics of this condition and may have implications for future research and clinical management.